1986
DOI: 10.1159/000199269
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the New H<sub>2</sub>-Receptor Antagonist Mifentidine on Gastric Secretion, Gastric Emptying and Experimental Gastric and Duodenal Ulcers in the Rat: Comparison with Cimetidine and Ranitidine

Abstract: The new H2-receptor antagonist mifentidine (DA 4577) was tested for its antisecretory and gastric motor effects in comparison with cimetidine and ranitidine. The Shay rat preparation (5 h) was used for studying gastric secretion; the gastric emptying of a liquid meal was chosen for studying gastric motility. All the three compounds inhibited acid secretion in a dose-dependent fashion. Calculated ED50s were 2.3, 12.2 and 92.8 mg·kg-1 for mifentidine, ranitidine and cimetidine, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…One hour after intravenous administration, dimaprit induced gastric damage in almost all the treated animals. As previously described (Scarpignato et al, 1986), this damage consisted of single prepyloric antral erosions. Both H2-antagonists were able to reduce ulcer incidence in a dose-dependent manner ( Figure 5).…”
Section: Evaluation Of Antiulcer Activitymentioning
confidence: 97%
See 2 more Smart Citations
“…One hour after intravenous administration, dimaprit induced gastric damage in almost all the treated animals. As previously described (Scarpignato et al, 1986), this damage consisted of single prepyloric antral erosions. Both H2-antagonists were able to reduce ulcer incidence in a dose-dependent manner ( Figure 5).…”
Section: Evaluation Of Antiulcer Activitymentioning
confidence: 97%
“…Since vagal stimulation following pylorus ligation in the rat causes mobilization of histamine (Code, 1982), this model appears to be suitable for the evaluation of antisecretory properties of H2-receptor antagonists and has been successfully employed in our laboratory to study new compounds of this type (Scarpignato et al, 1986 Gastric emptying was measured by a method previously described and validated (Scarpignato, 1983;Scarpignato et al, 1984;. The test meal consisted of 1.5 ml per rat of a prewarmed (350C) solution of phenol red (50mg dissolved in 100 ml of aqueous methylcellulose; 1.5% w/v).…”
Section: Measurement Of Gastric Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo and in vitro studies mifentidine Pagani et al, have shown the compound is a competitive H2-1985). Evidence suggests that mifentidine is at receptor antagonist (Bertaccini etal., 1984; Pagani least three times more potent than ranitidine in etal., 1985;Poli etal., 1984Poli etal., , 1985Giachetti etal., inhibiting gastric acid secretion Micheletti et al, 1985Micheletti et al, ) without significant 1985Scarpignato et al, 1985) and longer acting activity at H,-receptors (Montagna et al, 1982) than either cimetidine or ranitidine (Scarpignato or at cholinergic receptors (Bertaccini et al, et al, , 1986. In addition, the antiulcer activity against a variety of experimentallyinduced gastric and duodenal ulcers was found to be very high (Scarpignato et al, 1986;Del Soldato et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to set up a model of Hireceptor mediated gastric damage [4] to be used in the evaluation of antiulcer properties of Hi-receptor antagonists [11], we observed that ulcerogenic doses ofdimaprit (a selective H2-receptor agonist), administered intraperitoneally in rats, invariably cause signs of ab dominal discomfort, such as twisting, exten sion of hind limbs, turning and flexion of the trunk. These features are characteristic of the 'writhing phenomenon' that follows intraper itoneal injection of phenylquinone and other pain-causing substances commonly em ployed in analgesic tests [9].…”
Section: Introductionmentioning
confidence: 99%